Ministrial System in Islamic Political FIQH - Fathi Abdul Karim (Journal of Islamic Studies, 1981)
The paper starts by surveying the importance of the 'Ministry' and showing the linguistic origin of the word Wizara (Ministry). It then gives an historical intro¬duction in which it is shown that the arabs knew the system of Wizara before the advent of Islam, and that the history of the wizara system in Islam passed through two stages. The first one includes the early islamic period and the times of the Ummayyads. In this period the features of the wizara were not clear, the rules governing it were not definite, and the person responsible for it was not yet called Wazir (Minister). In the second stage, which begins with the advent of the Abbasid Caliphate all these matters were settled, and the wizara system was thus well established. The paper then goes on to deal with the rules governing the wizara, Fugaha, Jurists, used - according to the paper — to divide the wizara system into two types, the executive and the authoritative. The detailed rules governing each of these two divisions are enumerated. The paper ends with the following definite conclusions. The division of the wizara into executive and authoritative is not mandatory since it is not entailed by the fundamentals of Islam nor by any Is'amic principles of government. The entrustment of a minister with absolute authority is unacceptable since it is contrary to Islamic principles of government and to the Behaviour of the Comp¬panions of the Prophet. The entrustment of such a minister with unlimited jurisdiction and the unlawfulness of having more than one ministry — which, some jurists saw as a corollary of this unlimited jurisdiction are both unacceptable.